Altitudinal variation in diversity of Arctiidae and Saturniidae (Lepidoptera) in a Colombian Cloud Forest - MUÑOZ, ANDERSON; AMARILLO- SUÁREZ, ÁNGELA (Revista Colombiana de Entomología, 2010)
The richness and diversity of organisms is associated with environmental changes and factors such as altitude, determining the configuration of patterns of distribution of groups and species. In this study we compared the distribution and the richness of Arctiidae and Saturniidae (Lepidoptera) along an altitudinal gradient (1448-2068 m elev) in a cloud forest of the Department of Cauca, Colombia. These lepidopterans possess richness and life histories that are considerably different. We selected three altitudinal stations and in each one seven sampling events of six days each were conducted, between 6:00p.m. and 6:00a.m. We captured 70 species, 55 Arctiidae and 15 Saturniidae. The richness of Saturniidae decreased significantly with increasing altitude (Kruskal–Wallis P = 0.009), while the greatest richness of Arctiidae was at the middle altitude (Kruskal–Wallis P = 0.002). Alpha diversity had similar tendencies to that of richness for both families. Beta diversity in Saturniidae showed greater similarity between stations than the Arctiidae. Factors like resistance to environmental changes and the breadth of host plants of each group could explain the difference in the altitudinal distribution of diversity in these families.